(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
The evaluative functions play an important role in improving the quality of the teaching-learning process. Although the determinants of academic performance in higher education are known, the impact of evaluation processes on said improvement is unknown. Using statistical process control techniques, we seek to monitor and evaluate its capacity. In particular, the performance of students enrolled in economics and general economics was analyzed, for industrial engineering and electromechanical engineering careers, at the Santa Cruz Regional Faculty of the National Technological University. Data corresponding to the 2020 period were used and emphasis was placed on the failure rate. We observe that the failure rate is between 19 and 25%, respectively, for each of the cohorts analyzed, this result being representative for the data set. This novel finding serves as the basis for working on the quantification of teaching-learning processes. Thus, our results highlight the central importance of online execution of control charts, to follow the progress of the process and take the necessary corrective measures to achieve better results in the teaching-learning processes.